Comparison of the effectivity of oral and intra-articular administration of tenoxicam in patients with knee osteoarthritis - Erbas,Mesut (2015)
ABSTRACTBACKGROUND AND OBJECTIVES:Tenoxicam is widely used in osteoarthritis treatment and we aimedto compare the effectivity of oral and intra-articular administration of tenoxicam in osteoarthri-tis treatment.METHODS: This study was performed between 2011 and 2012 by retrospectively analyzing andcomparing the findings of 60 patients who were clinically and radiologically diagnosed with kneedegenerative osteoarthritis in Bünyan state hospital pain policlinic. 60 patients included in thestudy were divided into two groups. The first group (tenoxicam IA, n = 30) included patientfindings of those subjected to intra-articular injection of 20 mg tenoxicam to the knee oncea week for three weeks and the second group (oral tenoxicam, n = 30) included patients whowere administered 20 mg oral tenoxicam once a day for three weeks. All patients were clini-cally evaluated pre-treatment and in the 1st week, 1st month and 3rd month post-treatmentaccording to specified criteria.RESULTS AND CONCLUSIONS: Twenty two of 60 patients included in the study were male and 38were female. In both groups significant improvements were detected in all of the observedparameters: visual analog scale, Western Ontario McMaster Osteoarthritis Index (pain, physicalactivity, knee stiffness) and Lequesne index scores and in the evaluations performed in 1st week,1st month and 3rd month with respect to pre-treatment values. Besides, a better complianceto treatment and gastrointestinal system tolerability in tenoxicam IA group was also observed.Intra-articular tenoxicam administration could be thought as an alternative treatment methodin patients with knee osteoarthritis who cannot use oral tenoxicam especially due to systemicgastrointestinal system side effects and those who have difficulties in adapting to treatment.